2020
DOI: 10.1002/pbc.28744
|View full text |Cite
|
Sign up to set email alerts
|

Repeat‐positive SARS‐CoV‐2 in a child with cancer

Abstract: We report a case of repeat positivity with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in a child with cancer. The SARS-CoV-2 virus is responsible for the ongoing coronavirus disease 2019 (COVID19) pandemic. A 4-year-old male was treated for pre-B cell acute lymphoblastic leukemia (ALL) at our hospital. The patient was receiving treatment with the Indian Childhood Collaborative Leukaemia Group (ICiCLe) protocol under the high-risk arm. 1 On June 27, 2020, the patient and his caregiver tested p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 9 publications
(18 reference statements)
0
11
0
Order By: Relevance
“…In 29 studies ( n = 177 patients), 8,11–14,16–39 there was a mention of the type of test used to detect SARS‐CoV‐2. Among the 177 patients in these studies, PCR‐based tests were used to establish the diagnosis in 142 (one was also positive on CBNAAT) and antibody‐based tests in 23 (the type of test used was not mentioned for 12 patients in the study by Montoya et al 18 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In 29 studies ( n = 177 patients), 8,11–14,16–39 there was a mention of the type of test used to detect SARS‐CoV‐2. Among the 177 patients in these studies, PCR‐based tests were used to establish the diagnosis in 142 (one was also positive on CBNAAT) and antibody‐based tests in 23 (the type of test used was not mentioned for 12 patients in the study by Montoya et al 18 …”
Section: Resultsmentioning
confidence: 99%
“…In 196 patients (31 studies), 5,10–39 there was a mention about the type of malignancy, and 120 (53%) had hematological malignancies, and 76 (47%) had solid tumors. In studies that reported remission status (18 studies), 23 patients out of 47 were in remission from the underlying malignancy 10,11,14,20–26,29–37 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To et al and others [ [3] , [4] , [5] , [6] ] have recently reported reinfections with SARS-CoV-2 confirmed by genome sequencing. A few recent cases of potential reactivation with SARS-CoV-2 have been reported in cancer patients on chemotherapy [ [7] , [8] , [9] ], however were not confirmed by genetic characterization of the virus. Here we report results of genome sequencing in child with neuroblastoma reported previously by us as re-infected with SARS-CoV-2 after recovering fully and developing IgG antibodies [ 8 ].…”
mentioning
confidence: 99%